The Interpretation of Contextual Architecture in Designing Public Library in Balige - Tivany Simanjuntak; Morida Siagian (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Teachers, lecturers, students, and the community use the library as a knowledge and information resource in the context of implementing learning. A library is often thought of as a sizable book collection that is kept for the express purpose of gathering, maintaining, and dispensing books. Students can look up and gather the most recent scientific data in the library, which aids them with their assignments. People's preference for instant information via social media, especially students, is one of the reasons reading is becoming less popular these days. Aside from the fall in students' interest in reading, two other reasons why libraries are silent are their incapacity to adapt to the changing times and their failure to satisfy the demands of students. As a result, Balige must have a public library that can serve everyone in the city and can meet the demands of community activities. This Public Library design uses a contextual architectural approach to integrate various elements of the surrounding building facades.